2021
DOI: 10.1177/0194599820982910
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta‐analysis: Effectiveness of Corticosteroids in Treating Adults With Acute Vestibular Neuritis

Abstract: Objectives To determine whether steroids are effective in treating adults with acute vestibular neuritis. Data Sources PubMed, Embase, CINAHL, Cochrane CENTRAL, Web of Science, CAB Abstract, ICTRP, LILACS, PEDRO, ClinicalTrials.Gov, Google Scholar, NARIC, and OT Seeker. Review Methods A systematic review was undertaken for articles reporting subjective and/or objective outcomes of corticosteroids in adults with acute vestibular neuritis between December 2010 and October 2019. Reports of patient recovery from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 38 publications
0
41
0
2
Order By: Relevance
“…In accordance with guidelines for other inactivated vaccines, it is recommended to wait for at least 2 weeks after vaccination before a highdose course of systemic steroids is started [Soy et al (76) and personal information: Dr. Nadia Eberhard-Kuhn, Department of Infectious Diseases and Hospital Epidemiology, University Hospital Zurich]. As there is currently no high-quality evidence for the efficacy of systemic corticosteroids in AUPVP (77,78), the potential risks and benefits of starting a treatment should be balanced for each single patient. Consulting an immunologist or infectious disease specialist is useful in this context.…”
Section: Implications For Treatment and Further Covid-19 Vaccinationsmentioning
confidence: 99%
“…In accordance with guidelines for other inactivated vaccines, it is recommended to wait for at least 2 weeks after vaccination before a highdose course of systemic steroids is started [Soy et al (76) and personal information: Dr. Nadia Eberhard-Kuhn, Department of Infectious Diseases and Hospital Epidemiology, University Hospital Zurich]. As there is currently no high-quality evidence for the efficacy of systemic corticosteroids in AUPVP (77,78), the potential risks and benefits of starting a treatment should be balanced for each single patient. Consulting an immunologist or infectious disease specialist is useful in this context.…”
Section: Implications For Treatment and Further Covid-19 Vaccinationsmentioning
confidence: 99%
“…Both viral and vascular factors may contribute to AUV presentations. On the basis of a viral origin of AUV, a short course of corticosteroids may be indicated [37], although a very recent systematic review and meta-analysis concluded that there is insufficient evidence to support their use in AUV [38]. On the contrary, a retrospective study demonstrated that patients receiving a steroid treatment (methylprednisolone 1 mg/kg for 5 days with an additional 5 days of 0.5 mg/ kg) showed better results in terms of vestibular recovery and symptomatic relief/improvement compared to patients receiving non-glucocorticoid treatment [39].…”
Section: Acute Unilateral Vestibulopathy (Auv)mentioning
confidence: 99%
“…12 The analysis by Solis et al ( 2018) included four studies concluding that there is insufficient evidence to make a general recommendation for corticosteroid treatment. 13,19,22,24,27 Following our systematic analysis, the review by Leong et al 14 (2021) has been published. They included eight studies concluding that there is insufficient evidence to support the use of corticosteroids.…”
Section: Comparison With Previous Meta-analysesmentioning
confidence: 99%
“…They included eight studies concluding that there is insufficient evidence to support the use of corticosteroids. 14,[25][26][27][28][29][30][31]33 They focused on caloric recovery at various time points, results of the DHI and length of hospital stay. 14 The aim of our meta-analysis was to include all available studies, the older 17,18 and the newer ones.…”
Section: Comparison With Previous Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation